Efektivitas Project-Based Learning (PjBL) dalam Pembelajaran Matematika untuk Meningkatkan Kreativitas Siswa Sekolah Dasar: Systematic Literature Review - Galih Setyawati; Mutiara Nur Ekasari; Siti Aisyah; Wulan Izzatul Himmah (CV. Alim's Publishing, 2026)
This study aims to examine the effectiveness of implementing Project-Based Learning (PjBL) in mathematics instruction to enhance elementary school students' creativity, using a Systematic Literature Review (SLR) approach. The literature search was conducted through Google Scholar, SINTA, and DOAJ databases using relevant keywords. The initial search yielded 337 articles, which were then screened based on inclusion and exclusion criteria, resulting in 18 eligible articles for analysis. The selection process followed the PRISMA protocol to ensure transparency in the identification, screening, and data extraction stages. Inclusion criteria covered articles published between 2019–2025, indexed in SINTA, and addressing PjBL implementation in elementary mathematics learning. The findings reveal that PjBL has a significant positive impact on improving students' creativity across various topics, including fractions, measurement, data processing, and geometry. Through project-based activities, students developed contextual understanding, collaborative skills, and problem-solving orientation, while also demonstrating active participation, learning independence, and cooperative task completion. These findings confirm that PjBL is an effective instructional approach with strong potential for broader application in elementary mathematics education to optimally support students' creative development.